2022
DOI: 10.1111/evj.13586
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on cytokine concentration in equine autologous conditioned serum

Abstract: Background: Autologous conditioned serum (ACS) is a commonly administered intra-articular treatment for the management of osteoarthritis in athletic horses.Objectives: To investigate the influence of exercise on the concentration of cytokines in a non-commercial method of ACS production.Study design: Non-randomised cross over design.Methods: Whole blood was obtained from eight healthy Standardbred horses immediately prior to, 1 h and 24 h following a single bout of exhaustive exercise.Blood was processed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Some genes are characterized by a high reproducibility of both their induced expression and changed serum level of the proteins. This group includes the interleukins IL1B, IL1R2, and IL22RA2, whose genes were also expressed differentially in our study, as well as IL6, IL8, IL13, and IL17, which were found in other expression or enzyme studies [42][43][44][45][46]55,56,60,65,71]. Various studies on other serum values are interesting in this context.…”
Section: Gene Ontology Enrichment and Pathway Analysis Of Degssupporting
confidence: 64%
See 2 more Smart Citations
“…Some genes are characterized by a high reproducibility of both their induced expression and changed serum level of the proteins. This group includes the interleukins IL1B, IL1R2, and IL22RA2, whose genes were also expressed differentially in our study, as well as IL6, IL8, IL13, and IL17, which were found in other expression or enzyme studies [42][43][44][45][46]55,56,60,65,71]. Various studies on other serum values are interesting in this context.…”
Section: Gene Ontology Enrichment and Pathway Analysis Of Degssupporting
confidence: 64%
“…For example, well-trained horses showed an anti-inflammatory reaction after an 800 m race, while untrained horses showed a proinflammatory reaction, which is considered a training effect [42,65]. After an appropriate period of rest, these changes appear to return to normal, at least partially [44]. IL1RA, which correlates with cortisol concentration, appears to be of particular importance in restoring the homeostatic equilibrium [45].…”
Section: Gene Ontology Enrichment and Pathway Analysis Of Degsmentioning
confidence: 99%
See 1 more Smart Citation